Law and Morality in Perspective Sharia Economic Law - Opik Taupik; Hasan Bisri; Ayi Yunus Rusyana (Zona Law And Public Administration Indonesia, 2023)
In contemporary culture, morality and law are frequently debated topics, especially in relation to Islamic economic law. Within the framework of Islamic economic law, this paper will examine the concepts and definitions of morality and law and how they interact and work together. Using descriptive and analytical techniques, the author examines the principles of Islamic economic law that are based on moral ideals such as justice, openness, and honesty. The author's consideration of how law and morality are used in Islamic economic practice emphasizes the importance of compatibility or incompatibility between law and morality. These studies show the interaction between morality and law in various contexts, including in Islamic economic practice. Therefore, it is imperative to harmonize law and morality in the application of Islamic economics to achieve the desired outcome, which is the creation of justice and prosperity for society